STEPPER MOTOR CONTROL ANALYSIS USING ACCELERATION – DECELERATION METHOD BASED ON PLC (PROGRAMMABLE LOGIC CONTROL) - Budi Cahyo Wibowo; Mohammad Dahlan; R. Rhoedy Setiawan (Jurnal Media Elektrik, 2023)
Stepper motors are one of the motor variants that are widely used in the manufacturing sector. Stepper motors have the characteristic of being able to be controlled both speed and position control in an open loop control system. The method used to control the rotation of the stepper motor is to send a series of electrical pulses with a configuration of frequency values and number of electrical pulses so that the stepper motor can control the rotational speed and angular position of the motor. Acceleration-deceleration control applies a method of gradually changing the frequency of electrical pulses by increasing the frequency every 4mS until it reaches the target frequency value. By applying the acceleration-deceleration method, the stepper motor is capable of rotating at a speed of up to 3000 rpm and the motor rotation angle position is from 10o-360o precisely, this acceleration-deceleration method can rotate the motor at a controlled speed of up to 3000 rpm.